(untitled) (Global Journal of Science Frontier Research, 2012)
Efficiency of water treatment system grossly depends on the attenuation capacity of the filter media. Under natural condition, this capacity depends on the effects of physical, chemical and biological factors of which past works revealed few observation on physical factors under an explicit and simple experimental designs. In this work, we examined the variation of volume flux rate and porosity on the attenuation of migration of bacteria in sand media as can be applicable to water treatment system. Movement of Escherichia coli through matrix of different porosities in trends was studied in down – flow column experiment under natural and intermittent transport. Porosity values range between 0.28 and 0.42 while volume flux rate range between 0.82 x 10-4 m/s and 195.93 m/s respectively. The plot of normalized concentration versus volume flux was best fitted with polynomial curve of second degree which shows that attenuation of migration was partially varies with volume flux and not linear as revealed in past works. However attenuation of bacteria migration depends on the porosity as a function of depth ‘ɸ(x)’.